Proposal for an Enhanced Monitoring Technique for Active Control of Aircraft Flap Asymmetry - Leonardo Baldo; Matteo Davide Lorenzo Dalla Vedova; Jose Maria Cejudo Ruiz (Engineering Proceedings, 2025)
This paper presents an innovative active monitoring strategy to manage asymmetry in aircraft flaps. Complex mechanical systems like high-lift devices may undergo a wide range of faults, such as a broken transmission torsion bar or wear and tear on control surface actuators just to name a few. These faults can alter the surface symmetry between the two sides of the wing, potentially leading to dangerous conditions. The proposed relative dynamic position control technique provides a more effective monitoring method to detect and identify flap asymmetry. Once the faulty side has been identified, the system activates the wingtip brakes to halt the uncontrolled flap. The remaining functional flap is then moved to match the braking point of the failed flap, reducing the asymmetry. This approach effectively manages the unwanted roll moment caused by flap asymmetry, thereby partially restoring the aircraft’s maneuverability post-failure. The proposed monitoring technique has been subjected to extensive testing under various operational and failure conditions with the use of a mathematical model, with both new and worn actuators, and considering a wide range of possible failure scenarios.